Assessing privatization efficiency in CIS countries: Financial, non-financial, and GDP-linked indicators - Jun Chen; Talgat Yerzhanov; Svetlana Shcheglova; Anar Mirzayev (European Journal of Government and Economics (EJGE), 2023)
This study investigates the impact of privatization on the relationship between gross capital accumulation, employment, labor resources, government spending, and gross domestic product (GDP) in Commonwealth of Independent States (CIS) countries. Employing econometric analysis and cointegration evaluation, the study reveals that privatization has had a mixed impact on CIS economies. While privatization has contributed to increased capital accumulation and employment in some countries, it has also led to reduced labor resources and government spending in others. The study also finds that government spending is an indirect indicator of privatization efficiency that significantly influences GDP in Armenia, Azerbaijan, Kazakhstan, Kyrgyzstan, Moldova, Russia, Uzbekistan, and Tajikistan.
Keywords: L33; A10; O57; 330; capital accumulation; efficiency; GDP; government spending; privatization